2016
DOI: 10.1515/amtm-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Laser alloying of bearing steel with boron and self-lubricating addition

Abstract: 100CrMnSi6-4 bearing steel has been widely used for many applications, e.g. rolling bearings which work in difficult operating conditions. Therefore, this steel has to be characterized by special properties such as high wear resistance and high hardness. In this study laser-boriding was applied to improve these properties. Laser alloying was conducted as the two step process with two different types of alloying material: amorphous boron only and amorphous boron with addition of calcium fluoride CaF2. At first,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This process has not yet become part of the state-of-the-art. Recent publications in this area are mostly dealing with process development, research into microstructure and investigations on model test rigs [12][13][14][15][16]. Another field for buildup-welded materials by AM is the repair of worn machine elements such as shafts or bearings [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…This process has not yet become part of the state-of-the-art. Recent publications in this area are mostly dealing with process development, research into microstructure and investigations on model test rigs [12][13][14][15][16]. Another field for buildup-welded materials by AM is the repair of worn machine elements such as shafts or bearings [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of high-temperature wear of self-lubricating sintered steels with CaF 2 , MnS and TiC was studied in [27,28]. Studies have shown that MnS, TiC and CaF 2 additives significantly affect steel wear, while TiC improves its wear resistance.…”
Section: Introductionmentioning
confidence: 99%